Lower Permian Brachiopods from Wasp Head Formation, Sydney Basin, Southeastern Australia. (May 2014) - Cisterna, Gabriela A.; Shi, G. R.
Abstract : Although there is a generally accepted framework for the Permian marine biogeography of Australia, significant uncertainties remain concerning the temporal biogeographical changes closely related to the timing of Permian glacial–interglacial events. Several recent studies along these research lines demonstrate the importance of a reliable high-resolution biostratigraphical timescale for paleobiogeographical and paleoclimatic reconstructions. This paper provides, for the first time, a full taxonomic and biostratigraphical study of the brachiopod fauna from the Wasp Head Formation, southern Sydney Basin, southeastern Australia. The fauna is associated with deposits of the first Permian glacial interval suggested for eastern Australia. Three brachiopod assemblages are recognized. The lower and middle assemblages contain scarce brachiopods although associated bivalves are comparatively more common. Despite very low diversity and low abundance, these two brachiopod assemblages contain characteristic species of the Strophalosia concentrica and Strophalosia subcircularis brachiopod zones, both considered of late Asselian age. The third assemblage, occurring in the uppermost part of the formation, contains more brachiopods than bivalves and is referred to early Sakmarian in age. The species diversity and stratigraphic occurrences of the brachiopod assemblages in relation to sedimentary facies suggest that the lower two assemblages may represent an intra-glacial interval while the younger third assemblage, characterized by abundant occurrences of Trigonotreta and Tomiopsis species, accompanied by the bivalve Eurydesma, is more indicative of a post-glacial benthic marine fauna comparable to coeval brachiopod faunas found elsewhere in Gondwana.